Effects of different surgical treatments on children with ankyloglossia: protocol for a systematic review and meta-analysis - Chongqing Yu; Qi-Qi Li; Ruo-Zhen Zhang; Sheng-Lan Chen; Fei-Fei Xia; Zheng Zhou (BMJ Open)
Introduction Ankyloglossia is a situation where the tongue tip cannot go beyond the mandibular incisor because the frenulum linguae is short. It could affect children’s health by interfering with their ability to talk, breast feeding and dental development. The most effective measure to control ankyloglossia is the surgical method. However, which surgical procedure is the best one is still controversial. Thus, this protocol aims to assess the effectiveness of different surgical interventions in children with ankyloglossia.Methods and analysis PubMed, EMBASE, Cochrane Library, Web of Science and OVID will be searched for relevant information from inception to 31 May 2022. Observational studies in English that investigate the association between surgical methods and ankyloglossia will be included in this protocol. This protocol follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols. The Critical Appraisal Checklist for Analytical Cross-Sectional Studies and the Newcastle–Ottawa Quality Assessment Scale for longitudinal studies will be used to assess the included studies. The improvement of breast feeding and nipple pain will be the primary outcome. STATA V.15.1 will do the statistical analysis in the meta-analysis. Subgroup and meta-regression will be carried out based on the characteristics of included studies.Ethics and dissemination This systematic review and meta-analysis will summarise relevant information on the effects of different surgical treatments on patients with ankyloglossia. The results will be disseminated through peer-reviewed publications. The data included in this study will be extracted from the published original studies. Thus, ethical approval and informed consent will not be required.PROSPERO registration number CRD42022323350.